Factores estratégicos de éxito que inciden en el desarrollo organizacional en la iglesia Santiago de Machachi ubicada en el cantón Mejía ciudad de Machachi. - Jaguaco Erazo, Andrea Estefanía (2020)
This project aims to improve the limited organizational development processes presented at Santiago de Machachi Church through its strategic success factors for which a qualitative approach with a quantitative tendency, with correlational scope, was used as a methodology; also, the inductive-deductive and analytical-synthetic methods were used, with the data collection techniques: survey, interview and collation sheet, having a statistical assessment through the chisquare test which allowed to demonstrate that the application of success factors helps to improve Organizational Development. For this purpose, the SWOT diagnostic tool was used, which allowed determining the problems in the church by obtaining data that can guide managers on how to properly invest their resources, processes, and activities, obtaining support from their workers and collaborators. A Strategic Plan has been proposed with the formulation of the business philosophy and the strategic direction; besides, the development of a Balanced Scorecard where strategies were obtained with which is intended to improve the image of the church and the existing work environment in it, allowing users, workers and collaborators to feel completely satisfied.